A Contribution to the Research on the Boundary Between the Linear Pottery Culture Complex and the Balkano-Anatolian Groups of the Early Neolithic - Brukner, Bogdan (Balcanica - Annual of the Institute for Balkan Studies, 1988)
A Contribution to the Research on the Boundary Between the Linear Pottery Culture Complex and the Balkano-Anatolian Groups of the Early Neolithic